TREATMENT OF WARFARE AND ENVIRONMENTAL CATASTROPHE IN THE 21ST CENTURY: INSIGHTS FROM TED HUGHES’S POETRY - Dhariwal, Jaibir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
War machinery plays havoc on both human and non-human world. The 20th century in human history has witnessed two World Wars and various minor wars. Loss of human lives, widespread displacements, trauma, climate change, pollution, and habitat destruction underscore the catastrophe looming over the planet in 21st century. Ted Hughes, a renowned British poet, has been placed among the greatest poets of the second half of the 20th century. The present research explores how Hughes’s poetry reflects the destructive impact of warfare on the environment. The research also delves into the profound connection between war and the environmental crisis in the present century. Environmental poetics is anti-War in principle and practice. Drawing upon Environmental poetics and ecocritical theory, this paper seeks to contextualize Ted Hughes’s work within the broader environmental discourse of the present era. Hughes’s poetic language, imagery and symbolism reveals the brutality of war and its horrendous consequences on the natural world. The brutality of wars reflects the instinct and bloody side of modern people and modern society. His poetic oeuvre also provides a lens through which to view and contemplate the destructive potential of human behaviour and its impact on the natural environment.